SOSIALISASI PROLONGED JAUNDICE DAN KARTU WARNA TINJA UNTUK DETEKSI DINI ATRESIA BILIER PADA BIDAN DI JOMBANG - Bagus Setyoboedi; Martono Tri Utomo; Rendi Aji Prihaningtyas; Farahdina Farahdina; Firyal Nadiah Rahmah; Sjamsul Arief (Universitas Mataram, 2023)
The background of the activity is that the delay in the diagnosis of cholestasis in infants is still quite high. Biliary atresia is the most common cause of cholestasis in infants, which begins with prolonged jaundice. Early diagnosis of cholestatic infants can reduce mortality and morbidity and increase the prognosis and the cure rate. This activity aims to evaluate the level of knowledge about biliary atresia among primary health workers, including midwife in Jombang. This community service activity method was carried out in the form of socializing stool color cards for early detection of biliary atresia among midwife health workers at Jombang primary health facilities on March 10 2023. The socialization began with a pre-test and ended with a post-test. A total of 53 midwives at the Peterongan Jombang Community Health Center, East Java were involved in this activity. The average age was 35.02 ± 8.57 years and 33 respondents (62.3%) had worked more than five years. In their daily practice, most respondents (66%) rarely encounter infants who are still jaundice at more than 2 weeks of age. There was an increase in the level of knowledge about biliary atresia, shown by a pre-test score of 12.08 ± 1.9 and an increase in the post-test score of 13.7 ± 1.07. The level of knowledge about biliary atresia is not evenly distributed among health workers in primary health facilities, including midwife. Massive outreach is needed regarding early detection of biliary atresia.